PENGARUH PENILAIAN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN PT. MERAK SENTAUSA ABADI KABUPATEN BOYOLALI - Suwandi Suwandi; Dasmadi Dasmadi; Hari Purwanto (EKOBIS, 2021)
The study that has been conducted by the author aims to determine and prove whether or not the effect of job appraisal and work ability on the performance of PT. Merak Sentausa Abadi which is in Boyolali district. The research used is using quantitative research methods using data collection techniques using a questionnaire and also data from the literature. Similarly, the existing sample in the questionnaire data is 104 employees of PT. Merak Sentausa Abadi and using the questionnaire method directly. In this study, the authors used SPSS 20 to analyze data on multiple regression analysis techniques. Next, it can be seen from the effect of employee job appraisal on the ability of employees' performance to performance which affects the testing of the hypothesis. Seen at the final score, it is found that the percentage of Adjusted R Square is 42.6%, the variable of job appraisal with work ability affects the performance of employees. While the difference of 57.4% can be said to be influenced by other variables. The results of the author's research can be said that the ability and work assessment by partial test has a significant positive effect on the workings of the employees of PT. Sentausa Abadi Peacock.